Pengaruh Profitabilitas, Leverage, Arus Kas Terhadap Financial Distress (Pada Perusahaan Pertambangan Yang Terdaftar Dalam Bursa Efek Indonesia Periode 2017-2022) - Khotimah, Evi Nur; Gantino, Rilla (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyse the effect of Profitability, Leverage, and Cash Flow on Financial Distress in mining companies listed on the Indonesian Stock Exchange for the 2017 – 2022 period. In this study Profitability is proxied by Return On Assets (ROA), Leverage is proxied by Debt to Equity Ratio (DER), and Cash Flow is proxied by Operating Cash Flow (OCF). Meanwhile Financial Distress is proxied using Interest Coverage Ratio (ICR) with a formula comparing Earnigs Before Interest and Tax (EBIT) to interest expense. The sampling technique in this study used a purposive sampling technique. There are 13 mining companies registered in Indonesian Stock Exchange for the 2017 – 2022 period which are used as samples in this study. The type of data used is quantitive data from secondary data sourced from financial report. The data analysis method used is multiple linear regression analysis. The results of the study show that Profitability, Leverage, and Cash Flow simultaneously affect the Financial Distress. Partially Profitability and Cash Flow has a positive effect on Financial Distress. Meanwhile Leverage partially have no positive effect on Financial Distress.